ANALISIS PEMAHAMAN DAN PREFERENSI KEUANGAN SYARIAH DI KALANGAN GENERASI Z - Maharani, Nessa Okta Dwi; Shahri, Nurlaeli; Rosmawati, R (Jurnal Ekonomi & Bisnis, 2024)
This study explores the understanding and preferences for Islamic finance among Generation Z. Generation Z, as a cohort growing up in the digital age and globalization, plays an increasingly important role in global economic development. A qualitative research method is used to gain in-depth insights into this generation's financial perspectives and beliefs. The study used qualitative methods that aimed to gain in-depth insights into Generation Z's understanding and perspectives on syariah finance. The results of the study show that, generation Z has great potential to bring positive change to society through understanding and implementing Islamic financial principles. By understanding and implementing Islamic financial principles, they can become agents of change that create a more just, prosperous and sustainable society. They can inspire others by showing that financial success can be achieved without compromising Islamic values, and that wealth can be used for the greater good. The results of this study are expected to contribute to a better understanding of how syariah financial values ??can guide the global economic transformation towards greater sustainability and inclusivity.